2008
DOI: 10.1002/lsm.20589
|View full text |Cite
|
Sign up to set email alerts
|

Low‐energy laser irradiation increases endothelial cell proliferation, migration, and eNOS gene expression possibly via PI3K signal pathway

Abstract: Background and Objectives: The purpose of this study, therefore, was to determine the mechanisms by which lowenergy laser irradiation (LELI) may exert some of its angiogenic effects via the PI3 kinase/eNOS signaling pathway and induce endothelial cell migration and neovascularization, an important and necessary part of wound healing. Study Design/Materials and Methods: The possible molecular mechanism of helium-neon (He-Ne) laser irradiation on endothelial cells was proposed. He-Ne laser at 632.5 nm was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
86
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 62 publications
(59 reference statements)
9
86
2
5
Order By: Relevance
“…In addition to vasorelaxation, NO also regulates endothelial cell growth, migration, and apoptosis [17,18]. Consistent with results of the present study, a previous report also indicated that low-energy laser irradiation increased eNOS activity through phosphorylation of PI3K/Akt in human umbilical vein endothelial cells (HUVECs) [19].…”
Section: Irradiation With a 445 Nm Laser Contracted Aortic Rings By Asupporting
confidence: 92%
“…In addition to vasorelaxation, NO also regulates endothelial cell growth, migration, and apoptosis [17,18]. Consistent with results of the present study, a previous report also indicated that low-energy laser irradiation increased eNOS activity through phosphorylation of PI3K/Akt in human umbilical vein endothelial cells (HUVECs) [19].…”
Section: Irradiation With a 445 Nm Laser Contracted Aortic Rings By Asupporting
confidence: 92%
“…13,14,15,16,17,18,19 It is important to state that the increase of cell viability is a major issue for stem cells, primarily when the objective of stem cell culture is to implant them into human organs during cellular therapy. Several in vitro studies have already explored the effects of LPT on mesenchymal stem cells (derived from bone marrow and fat tissue).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cells with a lower pH than normal are more sensitive to LPT than those with parameters being optimal or close to it. 12,13,17,18,19,20 In this study, we used two different energy densities to analyze the effects of LPT on stem cells from deciduous teeth. Both protocols (i.e., 3 J/cm2 and 5 J/cm2) presented with significantly higher values of cellular proliferation compared with the negative control group (5% FBS).…”
mentioning
confidence: 99%
“…However, the molecular mechanisms underlying the biological effects induced by LLLI have not been thoroughly elucidated. Previous studies 14,15 show that LLLI regulates different biological processes and ultimately affects cell physiology by using different signaling pathways in different cell types. Previous studies also show that red light to near-infrared light is absorbed by the mitochondrial respiratory chain and the irradiation treatment led to increased production of reactive oxygen species (ROS), nitric oxide (NO), adenosine triphosphate (ATP), and cyclic adenosine monophosphate (cAMP).…”
Section: Introductionmentioning
confidence: 99%